Deformation and Failure Characteristics and Control Technology of Surrounding Rocks in Deep High-Horizontal Stress Rock Roadways in the Wanbei Mining Area - Chen, Denghong; Yuan, Yongqiang; Ma, Li (Frontiers in Earth Science, 2022)
Taking the engineering conditions of the Zhujixi coal mine and Hengyuan coal mine in the Wanbei mining area as the background, based on the investigation of the deformation and failure status of the surrounding rock of the two mines, the deformation and failure characteristics of the surrounding rock of the deep rock roadway in the Wanbei mining area are systematically studied by using the comprehensive research methods of the surrounding rock mechanical parameter test, in situ stress measurements, and numerical simulation. The results show that the measured value of the intermediate principal stress is slightly less than the theoretical value, which is obviously affected by the tectonic stress. The lateral pressure coefficients of the two mines calculated according to the theory are between 1.06 and 1.24 and 1.18 and 1.24, respectively. The simulation shows that when the lateral pressure is higher than 1.5, the arrangement of drilling holes with a depth of 5–10 m and a diameter of 200–300 mm can effectively transfer the stress concentration, proposed using Ф22 L = 2800 mm anchor rods, row spacing 800 × 800 mm, specification Ф 22. For the anchor cable with a length of L = 6,300 mm, the row spacing between anchor cables is 1,600 ± 100 mm, and the coordinated support technology of the reinforcement support and grouting is added. The technology can fully mobilize the deep stable rock stratum when it is applied from the slope change point of 11 coal belt roadways in the east wing of the Zhujixi coal mine to the machine head chamber of 11 coal belt roadways in the west wing, and the field application is good.